Symptom burden and outcomes of patients with platinum resistant/refractory recurrent ovarian cancer: a reality check: results of stage 1 of the gynecologic cancer intergroup symptom benefit study. - Friedlander, M; Stockler, M; O'Connell, R; Voysey, M; Oza, A; Gillies, K; Donovan, H; Martyn, J; Sjoquist, K; Butow, P; King, M (Lippincott Williams and Wilkins, 2014)
BACKGROUND: The aim of chemotherapy in patients with platinum resistant ovarian cancer is palliation. Patients' experience of symptoms is not well documented, and the impact of treatment on symptoms has not been evaluated in clinical trials. We report symptom burden and treatment outcomes from stage 1 of the Gynecological Cancer Intergroup (GCIG) Symptom Benefit Study. METHODS: One hundred twenty-six patients receiving palliative chemotherapy completed 5 validated health-related quality-of-life questionnaires before starting treatment and before each cycle. They also reported their expected and perceived benefits from treatment. Physicians documented the reasons for treatment and adverse events including symptoms at baseline and estimated the number of cycles of treatment that patients would receive. RESULTS: Palliation was the major reason for chemotherapy. At baseline, all patients were symptomatic (almost 70% had ≥9 symptoms). Patients had high expectation of benefit from treatment. Only 41% of patients received the predicted number of cycles with most stopping early (≤2 cycles) due to progression, death, or adverse effects. Treatment was associated with significant toxicity, with discordance between patient report and physician grading. Although RECIST response rates were low (8.5%), 40% of the patients were reported to have had a clinical benefit and almost 50% of symptomatic patients also reported symptom improvement. CONCLUSIONS: Patients had a complex array of symptoms and significant symptom burden, which was commonly the reason for treatment. Although chemotherapy improved symptoms in about half of the patients, many did not benefit and progressed rapidly. Our findings support research into the use of patient reported outcome measures to document symptoms, adverse events, and subjective benefit, both in clinical trials and in clinical practice, in this patient population. Our findings highlight the need to develop prognostic models to better select patients for treatment, and this is an aim of stage 2 of the GCIG Symptom Benefit Study.